Photocatalytic Activity and Antimicrobial Properties of TiO2-SiO2-PVA Composite - Wahyuni, Sri; Prasetya, Agung Tri; Kartini, Indriana (Asian Journal of Chemistry, 2016)
A series of silica-titania nanocomposite with different mole ratios was prepared in the presence of polyvinyl alcohol by the sol-gel method. Several characterization techniques were adopted such as N2-adsorption-desorption, X-ray diffraction, Fourier transform infrared spectroscopy, transmission electron microscope and scanning electron microscope connected with energy dispersive spectroscopy. The photocatalytic activity of the composites was investigated using methylene blue as a model pollutant. The results showed that the TiO2-SiO2 composites give a better performance than TiO2 alone. The TiO2-SiO2-30 composites (SiO2/TiO2 mole ratio = 0.3) gives the best result of methylene blue removal among the synthesized composites. The antimicrobial activity of the composites was evaluated by observing the inhibition of E. coli growth under UV irradiation at a wavelength of 368 nm. All nanocomposites give antimicrobial activity by inhibiting E. coli growth except the composite without UV irradiation.